Upaya Meningkatkan Kemampuan Membaca Permulaan dengan Menggunakan Metode Pembelajaran STAR Kelas 1 SDN Pabuaran Tumpeng 2 - Zuliani, Rizki; Lestari, Balqis Marta; Anggraeni, Rika (TSAQOFAH, 2023)
The most basic education learned by humans is reading, writing, and arithmetic. Especially reading lessons, reading the beginning of the initial steps of reading skills, with an emphasis on the process of reading activity, which will be a reference for initial reading is recording and decoding. Beginning reading learning is the level of the process of learning to read to master the writing system as a visual representation of language. For this reason, efforts that can be made are to foster students' reading interest, motivate students, choose STAR reading learning strategies for relevant reading learning, and improve students' creative thinking skills. The main and fundamental problem in this study is whether through the STAR method students' initial reading ability can be improved? The purpose of this study was to improve the beginning reading skills of grade 1 students at SDN Pabuaran Tumpeng 2 using the STAR method. To answer the problems above, the researcher conducted a class action research. This class action research design uses the STAR method in accordance with the class action research criteria. The data collected is through observation and tests at the end of each cycle. The methods used in this research are descriptive, communicative and qualitative methods.